Study of genetic parameters, correlation and path analysis for yield and quality characters in fine scented rice genotypes - Kondi, Ravi Kiran Reddy; Kar, Sonali; Mandawi, NC (ORYZA-An International Journal of Rice, 2022)
During kharif 2020, the Section of Genetics and Plant Breeding at S.G. College of Agriculture and Research Station, Jagdalpur, Bastar (C.G.), examined 41 fine scented rice genotypes for 21 yield, yield contributing, and quality parameters. For all of the characters investigated, ANOVA demonstrated that there was considerable variation among genotypes. PCV levels were discovered to be slightly greater than GCV values, indicating that the environment has an impact on character expression. Plant height, test weight, head rice recovery, grain length, grain width, grain L:B, kernel length, kernel width, kernel L:B, alkali spreading value, gel consistency, and amylose content all had strong heritability and GAM, showing additive gene action. Grain yield plot-1 was significantly correlated with panicle length, total number of filled grains per panicle-1, harvest index, test weight, grain width, kernel width, amylose content, alkali spreading value, kernel elongation ratio, number of effective tillers plant-1, and days to 50% flowering. Amylose content was found to have a positive relationship with alkali spreading value and kernel elongation ratio, but a negative relationship with gel consistency.At the genetic level, path coefficient analysis revealed that traits such as harvest index, number of effective tillers plant-1, grain width, number of tillers square meter-1, days to 50% blooming, and kernel width had true associations with grain yield plot-1. At the phenotypic level, panicle length, test weight, number of effective tillers plant-1, kernel width, days to 50% flowering, harvest index, and kernel elongation ratio all showed a genuine relationship with grain yield plot-1. As a result, selecting these parameters will boost grain yield in the long run.